Older Age and Abnormal Pulmonary Ventilation Function Do Not Increase the Risk of Pulmonary Hemorrhage Caused by CT-Guided Percutaneous Core Needle Biopsy. (5th August 2022) - Yu, Xuejuan; Li, Chunhai; Wang, Dexiang; Liu, Bo; Jia, Haipeng; Zhou, Wei
Abstract : Purpose . The aim of this study was to analyze the differences in risk factors for pulmonary hemorrhage in elderly and young patients with percutaneous computed tomography-guided needle biopsies (PCNBs). The correlations between the incidence of pulmonary hemorrhage and pulmonary function indicators before CT-guided PCNB were also discussed. Methods . Between January 2018 and December 2019, 1, 100 consecutive patients underwent CT-guided PCNBs at Qilu Hospital. Both univariate and multivariate logistic regression analyses identified risk factors for hemorrhage. Results . The occurrence of pulmonary hemorrhage was 22.1% in elderly patients and was 22.6% in young patients. In elderly patients, pulmonary hemorrhage was significantly influenced by needle depth to the lesion and dwell time, while in young patients, pulmonary hemorrhage was independently associated with lesion size, needle depth to the lesion, and dwell time. However, pulmonary function parameters, including FVC (% pred), FEV1 (% pred), FEV1 /FVC ratio (%), small airway function parameters (FEF50%, FEF75%, and FEF25–75% ), and large airway function parameters (MVV, PEF, and FEF25% ), were not risk factors for hemorrhage. Furthermore, the incidence of pulmonary hemorrhage was not associated with different types of pulmonary dysfunctions. The risk of pulmonary hemorrhage did not increase with the severity of pulmonary dysfunctions. Conclusions . In this study, age is no longer a risk factor in evaluating pulmonary hemorrhage. Longer needle depth to the lesion and longer dwell time were significantly high risk factors of hemorrhage in both elderly patients and young patients. Patients with severe pulmonary dysfunctions did not show increased risks of pulmonary hemorrhage here.